NEC-zero recommendations from scoping review of evidence to prevent and foster timely recognition of necrotizing enterocolitis - Gephart, Sheila M. (Matern Health Neonatol Perinatol, 2017)
BACKGROUND: Although decades have focused on unraveling its etiology, necrotizing enterocolitis (NEC) remains a chief threat to the health of premature infants. Both modifiable and non-modifiable risk factors contribute to varying rates of disease across neonatal intensive care units (NICUs). PURPOSE: The purpose of this paper is to present a scoping review with two new meta-analyses, clinical recommendations, and implementation strategies to prevent and foster timely recognition of NEC. METHODS: Using the Translating Research into Practice (TRIP) framework, we conducted a stakeholder-engaged scoping review to classify strength of evidence and form implementation recommendations using GRADE criteria across subgroup areas: 1) promoting human milk, 2) feeding protocols and transfusion, 3) timely recognition strategies, and 4) medication stewardship. Sub-groups answered 5 key questions, reviewed 11 position statements and 71 research reports. Meta-analyses with random effects were conducted on effects of standardized feeding protocols and donor human milk derived fortifiers on NEC. RESULTS: Quality of evidence ranged from very low (timely recognition) to moderate (feeding protocols, prioritize human milk, limiting antibiotics and antacids). Prioritizing human milk, feeding protocols and avoiding antacids were strongly recommended. Weak recommendations (i.e. “probably do it”) for limiting antibiotics and use of a standard timely recognition approach are presented. Meta-analysis of data from infants weighing <1250 g fed donor human milk based fortifier had reduced odds of NEC compared to those fed cow’s milk based fortifier (OR = 0.36, 95% CI 0.13, 1.00; p = 0.05; 4 studies, N = 1164). Use of standardized feeding protocols for infants <1500 g reduced odds of NEC by 67% (OR = 0.33, 95% CI 0.17, 0.65, p = 0.001; 9 studies; N = 4755 infants). Parents recommended that NEC information be shared early in the NICU stay, when feedings were adjusted, or feeding intolerance occurred via print and video materials to supplement verbal instruction. DISCUSSION: Evidence for NEC prevention is of sufficient quality to implement. Implementation that addresses system-level interventions that engage the whole team, including parents, will yield the best impact to prevent NEC and foster its timely recognition.